A Pragmatic Study of the Structure of Polite Language in Aviation Staff Communication - Susanthi, I Gusti Ayu Agung Dian; Warmadewi, Anak Agung Istri Manik; Kurnianto, Yohanes Tresno (Balai Bahasa Sulawesi Selatan, 2025)
This study examines the politeness strategies used by aviation staff when interacting with passengers at critical service points. Using a qualitative descriptive method with a relational pragmatic approach, data were collected from purposively selected YouTube videos showing interactions at immigration, security, and check-in counters. The videos were transcribed verbatim and analyzed using Brown and Levinson’s politeness theory, Searle’s speech act classification, and Locher and Watts’ relational work framework. The analysis focused on identifying interaction units, classifying speech acts, and examining politeness strategies and relational work. The findings show that aviation staff combine positive politeness (greetings, empathy), negative politeness (indirect requests, modals, hedges), and bald-on-record strategies (direct instructions) to balance institutional demands with interpersonal rapport. These strategies enhance passenger comfort, procedural clarity, and professional service identity. The study contributes to contextual pragmatics and provides practical guidance for developing culturally sensitive communication in aviation services. AbstrakPenelitian ini mengkaji strategi kesantunan yang digunakan staf penerbangan dalam berinteraksi dengan penumpang pada titik layanan kritis. Menggunakan metode deskriptif kualitatif dengan pendekatan pragmatik relasional, data diperoleh dari video YouTube yang dipilih secara purposif yang menampilkan interaksi di bagian imigrasi, keamanan, dan check-in. Video ditranskripsi secara verbatim dan dianalisis menggunakan teori kesantunan Brown dan Levinson, klasifikasi tindak tutur Searle, serta kerangka kerja relasional Locher dan Watts. Analisis dilakukan melalui identifikasi unit interaksi, klasifikasi tindak tutur, dan pemeriksaan strategi kesantunan serta kerja relasional. Hasil penelitian menunjukkan bahwa staf penerbangan memadukan strategi kesantunan positif (sapaan, empati), kesantunan negatif (permintaan tidak langsung, modal, peredam), dan strategi langsung (instruksi tegas) untuk menyeimbangkan tuntutan institusional dengan hubungan interpersonal. Strategi tersebut meningkatkan kenyamanan penumpang, kejelasan prosedur, dan citra layanan profesional. Temuan ini berkontribusi pada kajian pragmatik kontekstual dan memberikan panduan komunikasi sensitif budaya dalam layanan penerbangan.